Do voo da fênix aos mandamentos do peregrino: justiça reprodutiva e a presença negra nas ruas do Partenon em Porto Alegre/RS - Pereira, Milena Cassal (Universidade do Vale do Rio dos Sinos, 2023)
This thesis deals with the intertwining of the concept of Reproductive Justice, with the analysis of intersectionality, to understand the forms of confrontation and narratives of existence and resistance of four black people living on the streets in the Partenon, in Porto Alegre. Reproductive restrictions, racism, gender norms and violence, the invasion of bodies-territories and the Public Policy of Social Assistance are concepts that will be revisited to understand the different Reproductive Injustices, illustrating the scenario of discussions on Reproductive Justice.
Keywords: Justiça reprodutiva; Situação de rua; Racismo; Interseccionalidade; Gênero; Necropolítica; Políticas públicas; Reproductive justice; Homelessness; Racism; Intersectionality; Gender; Necropolitics; Public policy; ACCNPQ::Ciências Humanas::Sociologia